A single-layer photovoltaic encapsulation film and preparation method thereof
By grafting anti-PID monomers in polyolefin elastomers and copolymerizing with initiators, the potential-induced attenuation and additive precipitation problems in single-crystal PERC double-sided batteries are solved, and the anti-PID performance and compatibility of the adhesive film are improved. Higher storage stability and processing efficiency are achieved.
Patent Information
- Application Number
- CN202211361829.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-02
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-11-02
AI Technical Summary
The existing polyolefin elastomer encapsulation film is prone to potential induced attenuation (PID) in single-crystal PERC double-sided batteries, and is poorly compatible with polar additives, resulting in additive precipitation and storage stability problems.
By grafting anti-PID monomers in polyolefin elastomers, it increases its polarity and copolymerizes with initiators to form functional polyolefin elastomers. It is prepared by solution grafting method to reduce additive residue and slippage and improve phase Capacity and storage stability.
It improves the PID resistance of polyolefin elastomers, reduces additive precipitation, enhances compatibility with polar additives, improves processing efficiency and component preparation yield, and saves costs in an environmentally friendly manner.
Smart Images

Figure BDA0003922300460000021 
Figure BDA0003922300460000031 
Figure BDA0003922300460000041
Abstract
Description
Technical Field
[0001] The patent of this invention belongs to the field of photovoltaic applications and relates to a functional polyolefin elastomer and packaging film that is resistant to potential induced degradation. Background Art
[0002] Polyolefin elastomer POE is a thermoplastic elastomer that uses metallocene catalysts to achieve in-situ polymerization of ethylene and α-olefins. It has excellent water vapor barrier capability, weather resistance and high volume resistivity. It can ensure the safety of photovoltaic modules operating in high temperature and high humidity environments and long-term aging resistance. It is widely used in encapsulation film materials for photovoltaic modules.
[0003] Polyolefin elastomer encapsulation film is widely used in double-glass modules of monocrystalline PERC bifacial cells. Due to its bifacial power generation characteristics, back surface field passivation and local aluminum back surface field design, the back of the cell is particularly prone to potential induced degradation (PID), especially in double-glass modules. PID attenuation is more obvious. Although POE has excellent comprehensive performance, the anti-PID requirements of photovoltaic modules cannot be met by POE encapsulation film alone. A certain amount of anti-PID additives or water-absorbing fillers must be added to achieve the purpose of anti-PID of the film. Patents CN112680126A and CN106221592A provide an anti-PID film and preparation method. Although the anti-PID polar additive can achieve the effect of reducing PID, the anti-PID polar additive is still added in a blended manner, which will not produce obvious additive precipitation effect for polar polymer EVA, but the anti-PID effect of polyolefin film will be greatly reduced. Patent CN112824468A provides a composition of an anti-PID encapsulation film and a method for preparing an anti-PID encapsulation film, which achieves the purpose of reducing power attenuation by adding inorganic ion scavengers and inorganic oxides. However, the addition of inorganic substances will reduce the light transmittance of the film, reduce the light absorption efficiency of the battery cell, and also reduce the power generation power of the battery cell.
[0004] In order to improve the anti-PID performance of POE film and solve the problems of poor compatibility between POE and polar additives and easy precipitation during long-term storage, it is necessary to change the molecular chain structure of the POE matrix. At present, the main method for changing the molecular chain structure of POE is chemical grafting, specifically melt grafting and solution grafting. The melt grafting process is simple and can achieve continuous production, but the reaction temperature is high and not easy to control. The product grafting uniformity is poor, and cross-linking or degradation reactions are prone to occur. The prepared product is granular or block material, and unreacted monomers are not easy to remove. The solution grafting process has mild reaction conditions, the product grafting is more uniform, the grafting rate is easy to adjust, there are fewer side reactions, and the post-processing monomer removal is easier than the melt grafting method. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a single-layer photovoltaic encapsulation film and a preparation method thereof. The encapsulation film comprises a functional polyolefin elastomer that is resistant to potential induced decay. The polarity of the polyolefin elastomer can be increased, the absorption time of the additive can be reduced, and the processing efficiency can be increased; at the same time, it has better compatibility with the polar additive, and after being prepared into a finished film, the precipitation of the polar additive on the film surface can be reduced, the storage stability of the film can be improved, and the slippage of the film can be reduced, thereby improving the assembly preparation efficiency and yield.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] A single-layer photovoltaic encapsulation film comprises the following components in parts by weight:
[0008]
[0009]
[0010] The functional polyolefin elastomer of the present invention comprises the following components in parts by weight:
[0011] Polyolefin elastomer 100;
[0012] Anti-PID monomer 0.5-5, preferably 1.0-3.5;
[0013] The initiator is 0.05-2, preferably 0.05-1.0.
[0014] Furthermore, the polyolefin elastomer includes but is not limited to one or more of ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-pentene copolymer, and ethylene-octene copolymer; the polyolefin elastomer has a melt index of 1-40 g / 10 min and a melting peak temperature of 45-120° C.
[0015] Furthermore, the anti-PID monomer structure contains a double bond for grafting and an ether bond with one or more repeating units, such as an alkyl ether, an alkenyl ether, a cyclic ether, an aromatic ether or a mixed ether. Suitable examples include but are not limited to 4-allyl-2,6-dimethoxyphenol, 3,7-dimethyl-3-(1-ethoxyethoxy)-1,6-octadiene, 1,4-diallyl-2-butene, 2,5,8,11-tetraoxatetradecene, diethylene glycol divinyl ether, triethylhexane, diethylene glycol divinyl ether ... One or more of glycol divinyl ether, tetraethylene glycol divinyl ether, methyl 3,5-bis(allyloxy)benzene carboxylate, 4,4-diethoxy-1-butene, cyclohexyl vinyl ether, 1,4-butanediol divinyl ether, 2-(2-(vinyloxy)ethyl)isoindoline-1,3-dione, 2-[2-(vinyloxy)ethoxy]isoindoline-1,3-dione, 1-[2-(vinyloxy)ethyl]hydroxylamine, leaf alcohol acetal, and p-methoxystyrene.
[0016] Further, the initiator is an organic peroxide, including but not limited to one or more of dibenzoyl peroxide, dicumyl peroxide, tert-butyl peroxypivalate, diethylhexyl peroxydicarbonate and tert-butyl peroxy-2-ethylhexanoate.
[0017] The preparation method of the functional polyolefin elastomer of the present invention comprises the following steps: firstly dissolving the polyolefin elastomer in an organic solvent, then adding an anti-PID monomer and an initiator, and after the polymerization reaction is completed, using a flocculant to precipitate the reaction product from the polymerization reaction liquid, and after drying, extruding the functional polyolefin elastomer masterbatch through a single-screw extruder.
[0018] Taking ethylene-octene copolymer and 2,5,8,11-tetraoxa-tetradecene as examples, the reaction process for preparing functional polyolefin elastomer is as follows:
[0019]
[0020] Furthermore, the organic solvent is one or more of benzene, toluene, xylene, chlorobenzene, n-heptane, n-pentane, n-hexane and cyclohexane.
[0021] Furthermore, the flocculant is anhydrous ethanol.
[0022] The method for preparing the single-layer photovoltaic encapsulation film of the present invention comprises the following steps: functional polyolefin elastomer masterbatch, crosslinking agent, auxiliary crosslinking agent, antioxidant, tackifier, light stabilizer and ultraviolet absorber are uniformly mixed and then extruded through a single screw extruder.
[0023] Furthermore, the cross-linking agent is tert-butyl peroxide 2-ethylhexyl carbonate.
[0024] Furthermore, the auxiliary cross-linking agent is triallyl isocyanurate.
[0025] Furthermore, the tackifier is 3-(methacryloyloxy)propyltrimethoxysilane.
[0026] Furthermore, the antioxidant is n-octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate.
[0027] Furthermore, the light stabilizer is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
[0028] Furthermore, the ultraviolet absorber is 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The present invention grafts the anti-PID monomer into the main chain, which has a better utilization efficiency than directly adding the anti-PID monomer into the polyolefin elastomer in a blending manner, and at the same time avoids the residue of the anti-PID monomer in the packaging film, ensuring that the film has a long-term anti-PID performance.
[0031] 2. The present invention grafts polar anti-PID monomers into the main chain, which can increase the polarity of the polyolefin elastomer, reduce the absorption time of the additives, and increase processing efficiency; at the same time, it has better compatibility with polar additives. After being prepared into a finished film, it can reduce the precipitation of polar additives on the surface of the film, improve the storage stability of the film, reduce the slippage of the film, and improve the efficiency and yield of component preparation.
[0032] 3. The filtrate recovered after flocculation treatment of the present invention contains solvent, a small amount of monomer and ethanol. The ethanol and the solvent containing a small amount of monomer are separated from the filtrate, and are respectively distilled and purified for recycling, which is environmentally friendly and cost-saving. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] This embodiment adopts the solution grafting method, uses ethylene-octene copolymer as the grafting matrix, and 4-allyl-2,6-dimethoxyphenol as the grafting monomer to prepare the POE graft copolymer, and the specific preparation steps are as follows:
[0036] (1) A 5L stainless steel reactor was selected as the reactor, equipped with a stirrer, an automatic temperature control heating and cooling device, a nitrogen pipe, and a material thermometer; 3.1L xylene and 647g POE (Dow 8660) were added to the reactor, the temperature was raised to 60°C, and stirred at a speed of 280r / min for 2h to dissolve into a uniform POE glue solution;
[0037] (2) Add 16.94 g of 4-allyl-2,6-dimethoxyphenol monomer to the above POE glue solution and stir for 10 min to make the system a uniform solution; dissolve 6.49 g of dibenzoyl peroxide BPO in 0.1 L of xylene, mix well and add to the POE glue solution system, stir for 20 min to make it uniform; replace with N2 three times, raise the temperature of the reaction system to 100 ° C, stir at a rate of 320 r / min, and react for 16 h;
[0038] (3) After the reaction is completed, the glue solution is taken out and 4.8 L of anhydrous ethanol is added to cause the product to flocculate and precipitate from the solution; the recovered product is dried under vacuum at 90° C. to a constant weight to obtain a graft copolymer;
[0039] (4) The POE graft copolymer was extruded by a single screw extruder with a double cone feeder, and a functional polyolefin elastomer masterbatch with resistance to potential induced degradation was obtained by underwater pelletizing. The extruder speed was 45 r / min and the temperature was 90°C.
[0040] Example 2
[0041] Ethylene-butene copolymer (Dow 38680) was selected as the grafting base, and 1,4-diallyl-2-butene was used as the grafting monomer to prepare a POE graft copolymer, wherein the amount of 1,4-diallyl-2-butene monomer used was 10.82 g, and the remaining steps were the same as in Example 1 to obtain a POE graft copolymer.
[0042] Example 3
[0043] Ethylene-butene copolymer (Dow 38680) was selected as the graft base, and 2,5,8,11-tetraoxatetradecene was used as the graft monomer to prepare a POE graft copolymer, wherein the amount of 2,5,8,11-tetraoxatetradecene monomer used was 15.94 g, and the remaining steps were the same as in Example 1 to obtain a graft copolymer.
[0044] Example 4
[0045] Ethylene-butene copolymer (Dow 38680) was selected as the grafting base, and 2-(2-(vinyloxy)ethyl)isoindoline-1,3-dione was used as the grafting monomer to prepare a POE graft copolymer, wherein the amount of 2-(2-(vinyloxy)ethyl)isoindoline-1,3-dione used was 16.73 g, and the remaining steps were the same as in Example 1 to obtain a graft copolymer.
[0046] Example 5
[0047] Ethylene-butene copolymer (Dow 38680) was selected as the grafting matrix, and tetraethylene glycol divinyl ether was used as the grafting monomer to prepare a POE graft copolymer, wherein the amount of tetraethylene glycol divinyl ether monomer used was 16.87 g, and the remaining steps were the same as in Example 1 to obtain a graft copolymer.
[0048] Example 6
[0049] Ethylene-octene copolymer (Dow 8660) was selected as the grafting base, and 3,5-bis(allyloxy)benzenecarboxylate was used as the grafting monomer to prepare a POE graft copolymer, wherein the amount of 3,5-bis(allyloxy)benzenecarboxylate monomer used was 14.722 g, and the remaining steps were the same as in Example 1 to obtain a graft copolymer.
[0050] Example 7
[0051] Ethylene-octene copolymer (Dow 8660) was selected as the grafting base, and cyclohexyl vinyl ether was used as the grafting monomer to prepare a POE graft copolymer, wherein the amount of cyclohexyl vinyl ether monomer used was 14.36 g, and the remaining steps were the same as in Example 1 to obtain a graft copolymer.
[0052] Example 8
[0053] Ethylene-octene copolymer (Dow 8660) was selected as the grafting matrix and 1,4-butanediol divinyl ether was used as the grafting monomer to prepare a POE graft copolymer, wherein the amount of 1,4-butanediol divinyl ether monomer used was 9.705 g, and the remaining steps were the same as in Example 1 to obtain a graft copolymer.
[0054] The steps of preparing photovoltaic encapsulation film with the graft copolymer prepared in the above embodiment are as follows:
[0055] 100 parts by mass of functional polyolefin elastomer masterbatch with resistance to potential induced degradation, 0.8 parts by mass of tert-butyl peroxide 2-ethylhexyl carbonate, 0.5 parts by mass of triallyl isocyanurate, 0.2 parts by mass of 3-(methacryloyloxy)propyl trimethoxysilane, 0.2 parts by mass of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 0.1 parts by mass of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, and 0.1 parts by mass of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole were mixed evenly and added to a single-screw cast extruder. After the mixture was melted and plasticized, it was injected into a T-die, and a single-layer photovoltaic encapsulation film H1-8 was obtained through melt extrusion, cast film, cooling, slitting and winding.
[0056] Comparative Example 1
[0057] Ethylene-octene copolymer (Dow 8660) was selected as the grafting matrix and methyl acrylate was selected as the grafting monomer to prepare POE graft copolymer, wherein the amount of methyl acrylate monomer used was 1.68 g, and the remaining steps were the same as in Example 1 to obtain the graft copolymer. According to the above encapsulation film preparation steps, a single-layer photovoltaic encapsulation film W1 was obtained.
[0058] Comparative Example 2
[0059] A single-layer photovoltaic encapsulation film W2 was prepared by direct physical blending, wherein the film matrix was ethylene-butene copolymer (Dow 38680) particles, and 1.5 parts by mass of 1,4-butanediol divinyl ether was added. The single-layer photovoltaic encapsulation film W2 was prepared according to the above encapsulation film preparation steps.
[0060] Comparative Example 3
[0061] A single-layer photovoltaic encapsulation film W3 was prepared by direct physical blending, wherein the film matrix was ethylene-octene copolymer (Dow 8660) particles, 0.8 parts by mass of 2-ethylhexyl carbonate tert-butyl peroxide, and 0.5 parts by mass of triallyl isocyanurate. The single-layer photovoltaic encapsulation film W3 was prepared according to the above encapsulation film preparation steps.
[0062] The encapsulation films obtained by the above-mentioned embodiments and comparative examples were applied to the encapsulation of solar cell modules and evaluated by the following test methods. The evaluation results are listed in Table 1.
[0063] 1. Crosslinking degree
[0064] The test method refers to the China Photovoltaic Industry Association standard T / CPIA 0006-2017 "Copolyolefin Film for Photovoltaic Module Encapsulation".
[0065] Sample preparation: overlap two pieces of film, laminate them with a laminator, weigh 0.5g±0.01g, cut them into small particles with a size less than 3mm×3mm, and prepare 3 pieces for each group of samples.
[0066] After extraction with xylene at 140°C for 5 h, the mixture was placed in a vacuum oven at 140°C and dried to constant weight.
[0067] 2. Additive absorption time
[0068] Pour the resin and various additives into a transparent container, mix them evenly, and place them in a 50°C oven to observe whether there is any oily additive residue on the surface of the transparent container and the dryness of the particle surface. If there is no residue and the particle surface is dry, it means that the additives are completely absorbed.
[0069] 3. Amount of additive precipitation
[0070] 16 g of the film obtained by casting was weighed and placed in 160 g of anhydrous ethanol for 10 min. 5 g of anhydrous ethanol was taken for liquid chromatography testing to quantitatively analyze triallyl isocyanurate (TAIC) dissolved in the anhydrous ethanol.
[0071] 4. Light transmittance test
[0072] The test was carried out according to the spectrophotometer method of GB / T 2410-2008, and the average transmittance in the band range of 290nm~380nm and 380nm~1100nm was calculated respectively.
[0073] 5. Component power test
[0074] The films prepared in each embodiment and comparative example are used as the front and back packaging films of the same photovoltaic module. The photovoltaic module is composed of tempered glass, upper packaging film, double-sided crystalline silicon cell, lower packaging film, and tempered glass. Through a laminator, at 150°C, vacuum is first drawn and then pressurized, and cross-linked for 18 minutes. The power change of the test module before and after HAST (85°C, 85% RH, -1500V, 192h) aging is tested.
[0075] Table 1 Comparison of performance of encapsulation films prepared in Example and Comparative Example
[0076]
[0077] From the results, it can be seen that after the polyolefin elastomer is grafted with the anti-potential induced decay monomer, the film maintains a high degree of crosslinking, and the adjuvant absorption rate is <3.5h, and the adjuvant precipitation amount is <20ppm. In particular, after the grafting of large steric hindrance monomers such as benzene rings, the crystallinity of the polyolefin elastomer is reduced, and the light transmittance of the film is significantly improved. After 192h double 85 test, the front attenuation of the battery cell is <3%, and the back attenuation is <4%; after the anti-potential induced decay monomer is added by direct physical blending, the back attenuation is >5%, which is mainly because after the polyolefin main chain is grafted with double bond monomers, the anti-potential induced decay monomer is connected to the molecular chain through chemical bonds, and the thermal performance of the molecular chain is more stable; at the same time, the front and back potential induced decay of the battery component are small, which is mainly due to the role of the ether bond in the grafted monomer, and the oxygen atom in the ether bond is sp 3 Hybridization, where two orbitals are sp 3The hybrid orbitals overlap to form a σ bond, and the two unbonded orbitals contain two pairs of lone pairs of electrons. The electron-donating conjugation effect is greater than the electron-withdrawing induction effect, and metal cations can be adsorbed. Under the action of the potential difference, the metal cations are conducted along the molecular chain, so that the metal cations generated in the glass and the film will not enter the battery surface, thereby reducing the occurrence of PID-s and PID-p attenuation mechanisms of the bifacial PERC battery. At the same time, the two pairs of lone pairs of electrons on the oxygen atoms can form hydrogen bonds with water molecules as acceptors, reducing the entry of water into the battery surface, ensuring that the battery is not corroded, reducing the occurrence of PID-c attenuation mechanism, and ensuring that the battery has a higher power generation capacity.
Claims
1. A single-layer photovoltaic encapsulation film comprising the following mass parts: composition: The functional polyolefin elastomer comprises the following parts by mass: composition: Polyolefin elastomer 100; Anti-PID monomer 0.5~5; Initiator 0.05~2; The anti-PID monomer is selected from one or more of 4-allyl-2,6-dimethoxyphenol, 3,7-dimethyl-3-(1-ethoxyethoxy)-1,6-octadiene, 1,4-diallyl-2-butene, 2,5,8,11-tetraoxatetradecene, diethylene glycol divinyl ether, triethylene glycol divinyl ether, tetraethylene glycol divinyl ether, methyl 3,5-bis(allyloxy)benzene carboxylate, 4,4-diethoxy-1-butene, cyclohexyl vinyl ether, 1,4-butanediol divinyl ether, 2-(2-(vinyloxy)ethyl)isoindoline-1,3-dione, 2-[2-(vinyloxy)ethoxy]isoindoline-1,3-dione, 1-[2-(vinyloxy)ethyl]hydroxylamine, leaf alcohol acetal, and p-methoxystyrene; The preparation method of the functional polyolefin elastomer comprises the following steps: firstly dissolving the polyolefin elastomer in an organic solvent, then adding an anti-PID monomer and an initiator, and after the polymerization reaction is completed, using a flocculant to precipitate the reaction product from the polymerization reaction liquid, and after drying, extruding the functional polyolefin elastomer masterbatch through a single-screw extruder.
2. The single-layer photovoltaic encapsulation film according to claim 1, comprising the following components in parts by weight:
3. The single-layer photovoltaic encapsulation film according to claim 1, characterized in that: The functional polyolefin elastomer comprises the following parts by mass: composition: Polyolefin elastomer 100; Anti-PID monomer 1.0~3.5; Initiator 0.05~1.
0.
4. The single-layer photovoltaic encapsulation film according to claim 1, characterized in that: The polyolefin elastomer is selected from one or more of ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-pentene copolymer and ethylene-octene copolymer; the polyolefin elastomer has a melt index of 1-40 g / 10 min and a melting peak temperature of 45-120° C.
5. The single-layer photovoltaic encapsulation film according to claim 1, characterized in that: The flocculant is anhydrous ethanol.
6. A method for preparing the single-layer photovoltaic encapsulation film according to any one of claims 1 to 5, comprising the following steps: Functional polyolefin elastomer masterbatch, crosslinking agent, co-crosslinking agent, antioxidant, tackifier, light stabilizer and ultraviolet absorber are mixed evenly and then extruded through a single screw extruder.
7. The method according to claim 6, characterized in that The cross-linking agent is tert-butyl peroxide 2-ethylhexyl carbonate; and the auxiliary cross-linking agent is triallyl isocyanurate.
8. The method according to claim 6, characterized in that The adhesion promoter is 3-(methacryloyloxy)propyltrimethoxysilane.
9. The method according to claim 6, characterized in that The antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate; the light stabilizer is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate; and the ultraviolet absorber is 2-(2'-hydroxy-5'-methylphenyl) benzotriazole.
Citation Information
Patent Citations
Anti-PID (potential induced degradation) packaging adhesive film and preparation method thereof
CN106221592A
High-resistance PID packaging adhesive film and preparation method thereof
CN112680126A
Composition for forming anti-PID packaging adhesive film, anti-PID packaging adhesive film and solar module
CN112824468A
Multi-layer composite photovoltaic packaging adhesive film resistant to PID (potential induced degradation) as well as preparation method and application
CN109337599A
Anti-PID POE adhesive film specifically for photovoltaic double-glass assembly packaging and preparation method therefor
WO2021238116A1
Cited By
Adhesive film composition and application thereof
CN122278382A